HR MANAGEMENT IN THE GREEN ECONOMY: EXPERIENCES FROM SCANDINAVIAN COUNTRIES, JAPAN AND SINGAPORE - Aralbayeva Bibijan Kuralbayevna, Suyunov Dilmurod Kholmuradovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This paper explores the integration of Human Resources (HR) management practices in the green economy, focusing on international experiences from Scandinavian countries, Japan, and Singapore. It highlights the scientific novelty of these practices, references insights from renowned scholars, and provides data-driven comparisons through tables. The study aims to offer a comprehensive understanding of how green HR initiatives can enhance organizational sustainability and effectiveness.